The Role of Mobile Forensics as Electronic Evidence in Proving Murder Cases - Andreas Bintang Raja Sihombing; Patrisia Tanwijaya; Najla Azrijal Chosaf; Michelle Evelyn Marpaung; Keisha Zahra Wibowo; Dyo Ganda Siadari; Dinda Aurelia Rosi Nasution; Boy Gabriel Yohanes Simarmata; Ariel Alexander; Yuni Priskila Ginting (West Science Law and Human Rights, 2026)
This study examines the role of mobile forensics as electronic evidence in proving murder crimes in Indonesia amidst the increasing complexity of crimes and perpetrators' efforts to eliminate digital traces. The study uses a normative juridical method with a descriptive-analytical approach through a literature review of relevant laws and regulations, court decisions, and scientific literature. The results of the study indicate that mobile forensics has an important position in the criminal evidence system because it is able to produce legally valid electronic information and/or electronic documents as recognized in the Criminal Procedure Code, the ITE Law, and strengthened by Constitutional Court Decisions. In murder cases, mobile forensics plays a strategic role in tracing communications, locations, metadata, and digital activities to reconstruct the chronology of events, identify the perpetrator, and strengthen the judge's conviction. However, the strength of its evidence is highly dependent on the authenticity, integrity, and reliability of the data, as well as compliance with legal procedures such as chain of custody, lawful seizure, and the involvement of digital forensic experts. This study concludes that mobile forensics has become an important instrument in modern criminal law evidence, but its optimization still faces challenges in the form of lack of uniform operational standards, limited human resources, and the need to strengthen regulations to create legal certainty, justice, and effective law enforcement in the digital era.